Global priorities for research and the relative importance of different research outcomes: an international Delphi survey of malaria research experts - Mulligan, Jo-Ann (Malar J, 2016)
BACKGROUND: As global research investment increases, attention inevitably turns to assessing and measuring the outcomes and impact from research programmes. Research can have many different outcomes such as producing advances in scientific knowledge, building research capacity and, ultimately, health and broader societal benefits. The aim of this study was to test the use of a Delphi methodology as a way of gathering views from malaria research experts on research priorities and eliciting relative valuations of the different types of health research impact. METHODS: An international Delphi survey of 60 malaria research experts was used to understand views on research outcomes and priorities within malaria and across global health more widely. RESULTS: The study demonstrated the application of the Delphi technique to eliciting views on malaria specific research priorities, wider global health research priorities and the values assigned to different types of research impact. In terms of the most important past research successes, the development of new anti-malarial drugs and insecticide-treated bed nets were rated as the most important. When asked about research priorities for future funding, respondents ranked tackling emerging drug and insecticide resistance the highest. With respect to research impact, the panel valued research that focuses on health and health sector benefits and informing policy and product development. Contributions to scientific knowledge, although highly valued, came lower down the ranking, suggesting that efforts to move research discoveries to health products and services are valued more highly than pure advances in scientific knowledge. CONCLUSIONS: Although the Delphi technique has been used to elicit views on research questions in global health this was the first time it has been used to assess how a group of research experts value or rank different types of research impact. The results suggest it is feasible to inject the views of a key stakeholder group into the research prioritization process and the Delphi approach is a useful tool for eliciting views on the value or importance of research impact. Future work will explore other methods for assessing and valuing research impact and test the feasibility of developing a composite tool for measuring research outcomes weighted by the values of different stakeholders. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12936-016-1628-4) contains supplementary material, which is available to authorized users.